Prenatal Care Adherence and Neonatal Intensive Care Unit Admission or Stillbirth among Women with Gestational and Preexisting Diabetes Mellitus - Sperling, Jeffrey D.; Maggio, Lindsay; Has, Phinnara; Daley, Julie; Khander, Amrin; Coustan, Donald R. (American Journal of Perinatology, 2018)
Objective To determine if there was an association between prenatal care adherence and neonatal intensive care unit (NICU) admission or stillbirth, and adverse perinatal outcomes in women with preexisting diabetes mellitus (DM) and gestational DM (GDM).Materials and Methods This is a retrospective cohort study among women with DM and GDM at a Diabetes in Pregnancy Program at an academic institution between 2006 and 2014. Adherence with prenatal care was the percentage of prenatal appointments attended divided by those scheduled. Adherence was divided into quartiles, with the first quartile defined as lower adherence and compared with the other quartiles.Results There were 443 women with DM and 499 with GDM. Neonates of women with DM and lower adherence had higher rates of NICU admission or stillbirth (55 vs. 39%; p = 0.003). A multivariable logistic regression showed that the lower adherence group had higher likelihood of NICU admission (adjusted odds ratio: 1.61 [1.03–2.5]; p = 0.035). Those with lower adherence had worse glycemic monitoring and more hospitalizations. Among those with GDM, most outcomes were similar between groups including NICU admission or stillbirth.Conclusion Women with DM with lower adherence had higher rates of NICU admission and worse glycemic control. Most outcomes among women with GDM with lower adherence were similar.
Keywords: gestational diabetes mellitus; prenatal care adherence; preexisting diabetes mellitus; NICU admission; glycemic control; pregnancy